IDENTIFICAÇÃO DE NECESSIDADES PALIATIVAS, ASPECTOS CLÍNICOS E FUNCIONAIS DE PACIENTES COM DPOC - VITÓRIA TAISE DA CRUZ (2023)
Identification of patients diagnosed with COPD who require palliative care, analysis of clinical and functional aspects.